Saberes dos professores de filosofia de ensino médio : entre a formação e prática - Godói, Priscylla Krone Martins Coratti Sarsano de (2013)
The main aim of this work is to understand the teaching expertise of Brazilian High School Philosophy teachers, with regard to training requirements and teaching practices. Based on the philosophical ideas developed in the Brazilian historical educational context by Cartolano (1985), Alves (2002, 2009a, 2009b), Horn (2009), Gonçalves (2011) and Palma Filho (2011), and an analysis of official documents (BRASIL, 1998, 1999, 2002 and 2006; SÃO PAULO, 2008, 2011), this work discuss the current status of Philosophy as a subject in official documents and in the curriculum of São Paulo schools. It also has its foundations in theoretical references such as Lorieri (2002), Aspis (2004), Saviani (2004), Ghedin (2008), Cerletti (2009), Severino (2011) and Gallo (2012), in respect to teaching and the Philosophy teacher, in addition to those authors who deal with teacher training, knowledge and practice, such as Cunha (1997), Abdalla (2006), Rios (2010a, 2010b), Tardif (2012) and, above all, Gimeno Sacristán (1995), regarding the established practice system. The research follows a methodological approach of a qualitative nature, using a questionnaire to interview 25 Philosophy teachers from private and public schools in São Paulo State. All collected data was analyzed using the content analysis technique (BARDIN, 2011), and regrouped into six thematic axes: academic training, knowledge of the documents which form the basis of the teacher¿s work; the perception of teaching, the perception of the teaching reality; techniques and practice and continued professional training. The results show: 1st, knowledge related to professional training (for those who do not have a specific graduation in Philosophy); subject expertise, which relates theory and practice and is the fundamental basis for pedagogical action, curriculum knowledge which reveals the importance of actions inside and outside the classroom; and experiential knowledge, which forms the basis of and accompanies the process of teacher training, experience and performance; 2nd, knowledge acquired during training and educational practice, which constitutes a professional identity for this teacher; and 3rd, the need to reflect on how to overcome difficulties regarding school structure, work conditions, investment in continued training and the use and improvement of new technology.